2021
DOI: 10.1002/adfm.202008328
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy of Discretionarily Reconfigurable Actuators Based on Self‐Healing Elastomers for Diverse Soft Robots

Abstract: Actuators have shown great promise in many fields including soft robotics. Since reconfiguration allows actuators to change their actuation mode, it is considered a key characteristic for new‐generation adaptive actuators. However, it remains a challenge to design simple and universal methods to fabricate actuators that can be reconfigured to allow diverse actuation modes. Here, a macroscopically discretionary healing‐assembly strategy to fabricate reconfigurable soft actuators based on intrinsic self‐healing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 50 publications
0
39
0
1
Order By: Relevance
“…Next, we demonstrate that a single GO mesotube can be used as a multifunctional sensor for perceiving vibration, temperature, and human artery pulse pressure. Because the GO mesotubes operate as a sensor in wet conditions, they are highly likely to be used as soft robotics [26][27][28][29] or electronic skin. [30][31][32][33] Recently, flexible, affordable, and elastic wearable electronics have been highlighted for monitoring human biomedical signals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we demonstrate that a single GO mesotube can be used as a multifunctional sensor for perceiving vibration, temperature, and human artery pulse pressure. Because the GO mesotubes operate as a sensor in wet conditions, they are highly likely to be used as soft robotics [26][27][28][29] or electronic skin. [30][31][32][33] Recently, flexible, affordable, and elastic wearable electronics have been highlighted for monitoring human biomedical signals.…”
Section: Resultsmentioning
confidence: 99%
“…The GO mesotubes behaved like a soft gel with a Young's modulus of 974 Pa and were robust to 10 5 cycles of bending tests, rendering them promising candidates as wet sensors for soft robotics [26][27][28][29] and electronic skins. [30][31][32][33] As a proof of concept, we demonstrated that a single GO mesotube can be used as a wet-conditioned sensor for monitoring mechanical vibration and human artery pulse pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [ 185 ] Copyright 2021, Wiley‐VCH. b) Heart with LEDs that can light up, incorporating a conductive self‐healing polymer.…”
Section: (Re‐)assembly and Bindingmentioning
confidence: 99%
“…However, with reversible (physico)chemical bonds these couplings can be made reversibly and modules can be separated from the system by mechanical force, for example, cutting. Lou et al [185] used the stacking technique (Section 4.1) to manufacture reconfigurable bilayer actuator modules for soft robotics, composed of two layers of elastomers based on reversible poly(dimethylglyoxime-urethane) and hydrogen bond cross-links that differ in cross-link density (Figure 8a). The bilayer actuator responds to a solvent stimulus (chloroform) due to the difference in the cross-linking densities of the two layers.…”
Section: Reassembly Of Modular Systemsmentioning
confidence: 99%
“…However, these soft connections perform low-alignment precision and require extra actuation appendages resulting in the complexity of systems. In addition, adhesive connections, including glued adhesion, [30][31][32][33] hot-melt adhesion, [34,35] and self-healing elastomer, [36][37][38][39] are connection methods without introducing any rigid or soft connection counterparts. However, these connections either are irreversible permanent connections or still need extra actuation appendages.…”
mentioning
confidence: 99%